Preparation and application of high-performance bowl-shaped tungsten oxide gas-sensitive material
By using ammonium paratungstate and PVA to prepare bowl-shaped WO3 materials, the problem of insufficient selectivity and sensitivity of dimethylamine gas in the prior art is solved, and a high-performance gas-sensitive sensor without precious metal doping is realized, with fast Responsive and highly sensitive performance, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411331909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has failed to prepare WO3 materials with special crystal phase structure with high selectivity and sensitivity to dimethylamine gas by regulating reaction raw materials, and the preparation method of high-performance gas-sensitive sensors has precious metal doping, high cost and complexity. Problems with technology.
Using ammonium paratungstate and PVA as raw materials, bowl-shaped WO3 material is prepared by spray drying and high-temperature calcination to form a crystal phase structure with high exposure surface, increasing the reaction area, and achieving the preparation of low-cost, high-performance sensor materials without precious metal doping.
The prepared sensors have fast response, low detection line and high sensitivity, and show excellent selectivity and repeatability to dimethylamine, and are suitable for industrial production, environmental monitoring and food quality inspection and other fields.
Smart Images

Figure CN119143182A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas-sensitive materials, and in particular to the preparation and application of a hollow bowl-shaped tungsten oxide material composed of particles having high selectivity for dimethylamine gas and having a (020) high-exposed surface crystal phase. Background Art
[0002] With the rapid development of the global economy and the accelerated advancement of industrialization, environmental pollution and toxic gas emissions have become serious social problems. In order to effectively monitor and control the concentration of harmful gases in the atmosphere, gas sensors have received widespread attention and application as an important detection method. Dimethylamine (DMA) is a colorless, volatile gas. Its physical state is in a gaseous state at room temperature, with a melting point of about −92°C and a boiling point of about −7°C. Dimethylamine gas is widely present in aquatic products, fermented products, rubber and leather production sites, causing serious harm to food safety and human health. It has a pungent odor. High concentrations of dimethylamine can cause irritation to the eyes, nasal cavity and respiratory tract. The harm caused by dimethylamine to human health is mainly manifested through inhalation or skin contact. Long-term contact may increase the risk of cancer, especially for respiratory tumors. It has a potential carcinogenic effect. Gas sensors can generate corresponding electrical signals in response to changes in the concentration of the target gas, thereby realizing rapid detection and quantitative analysis of harmful gases.
[0003] Metal oxide semiconductor gas sensors have the advantages of fast response speed, high sensitivity, relatively simple preparation process and low cost, and are often integrated with other devices and widely used. The currently recognized gas sensing mechanism is that when the target gas molecules are adsorbed onto the surface of the material, the conductivity of the material changes due to the transfer of electrons. Common metal oxides include tungsten oxide (WO3), zinc oxide (ZnO), indium oxide (In2O3), etc. In particular, WO3 has attracted widespread attention due to its chemical stability, structural diversity and easy regulation. WO3 is a typical n-type semiconductor with a band gap of about 2.4-2.8 eV. WO3 with various morphological structures has been used in gas sensors, including nanowires, nanospheres, nanoflowers and layered nanosheets.
[0004] WO3 has a variety of crystal phases (such as monoclinic phase, orthorhombic phase, tetragonal phase, etc.), and different crystal phases have different thermodynamic stability and reactivity. For example, some crystal phases are more stable at higher temperatures and are suitable for gas sensors working in high temperature environments. The arrangement and density of atoms on different crystal planes are different, which affects the ability to adsorb gas molecules. For example, some crystal planes have higher adsorption energy for specific gas molecules, thereby improving gas-sensitive selectivity and sensitivity. Different crystal planes may have different numbers and types of defects and active sites, which are key to the adsorption and reaction of gas molecules. For example, exposing more oxygen vacancies can enhance the adsorption of oxygen, thereby improving the sensitivity to reducing gases (such as CO, H2). WO3 in different crystal phases has different electronic structures and band gaps, which will affect the changes in its conductivity and sensitive resistance. For example, a crystal phase with a smaller band gap may produce a more significant conductivity change when a gas molecule is adsorbed, thereby improving sensitivity.
[0005] By controlling the synthesis conditions (such as doping, temperature, precursors, reaction time, etc.), specific crystal planes can be preferentially exposed, thereby optimizing the gas sensing properties of WO3. For example, some studies have shown that WO3 nanomaterials with specific crystal planes can be obtained through hydrothermal synthesis, thereby improving the sensitivity to ammonia. By precisely controlling the temperature and atmosphere during the synthesis process, WO3 with a specific crystal phase can be synthesized. For example, by controlling the sintering temperature, WO3 with different crystal phases can be obtained, thereby adjusting its gas sensing properties.
[0006] The crystal plane and crystal phase structure have a significant impact on the gas-sensitive selectivity and sensitivity of tungsten oxide. The performance of WO3 gas sensors can be significantly improved by fine control of the crystal plane and crystal phase. This optimization not only helps to improve the sensitivity and selectivity of the sensor, but also expands its application range in different gas detection. At present, there is no report on the preparation of WO3 with a special crystal phase structure that has high selectivity and sensitivity to dimethylamine gas by regulating the reaction raw materials without doping. Summary of the invention
[0007] In view of the shortcomings of the prior art, the first technical problem to be solved by the present invention is to provide a method for preparing a bowl-shaped WO3 material composed of particles for high-performance sensors and its application, and then add PVA to form particles on the surface of the prepared WO3 material, thereby increasing the reaction area. The material of the present invention does not require precious metal doping, has low production cost and is environmentally friendly, has a simple synthesis route, high repeatability, and the preparation method can achieve mass production.
[0008] The second technical problem to be solved by the present invention is to provide an application of a material for dimethylamine gas sensor in the preparation of sensor devices. The excellent gas sensing ability can be attributed to the change of PVA on the morphology and structure of WO3. PVA makes the surface of WO3 material have a large number of protruding particles, thereby increasing the reaction area and having a high (020) exposed crystal plane. This technology has far-reaching market application prospects in the fields of industrial production, environmental monitoring, indoor air quality monitoring, safety protection, and food quality testing.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a preparation method of a material for a high-performance sensor and its application. Specifically, a bowl-shaped WO3 material is designed. The preparation scheme uses ammonium paratungstate and PVA as raw materials, and is prepared by spray drying and high-temperature annealing. It includes the following steps: ① Add ammonium paratungstate to deionized water and stir for 2 h; ② After adding PVA, heat and stir evenly, and magnetically stir for 4 h; ③ Spray dry the mixed solution; ④ Heat the powder to dry and calcine to obtain WO3 gas sensitive material.
[0010] Specifically, the addition amount of PVA in step 2 is 0-0.4g; the spray drying inlet temperature in step 3 is 80-95℃, the outlet temperature is 140-160℃, and the flow rate is 100-200mL / h; the calcination temperature in step 4 is 350-450℃, and the calcination time is 1-5h. It is also characterized in that the diameter of the bowl-shaped WO3 composed of the particles ranges from 3 to 5 microns; the specific surface area is 10-50 m 2 / g; has a (020) high exposed surface crystal phase structure.
[0011] According to the above requirements and preparation scheme, the obtained WO3 was prepared into a sensor device for use in a sensor. The prepared sensor has a fast response, a low detection line (1ppm), and a high sensitivity value (74) when exposed to 50 ppm dimethylamine. The sensor also exhibits excellent selectivity and repeatability. Beneficial Effects
[0012] Compared with the prior art, the preparation method and application of a dimethylamine gas sensor material of the present invention have the following advantages: due to the addition of PVA, a large number of particles are formed on the surface of the WO3 material to accumulate into a porous hollow structure, and the existence of the structure increases the reaction area. The material of the present invention does not require precious metal doping, has low production cost and is environmentally friendly, has a simple synthesis route and high repeatability. The prepared sensor has a fast response, a low detection line (1 ppm), and a high sensitivity value (74) when exposed to 50 ppm dimethylamine. The sensor also exhibits excellent selectivity and repeatability. The excellent dimethylamine gas sensing can be attributed to the (020) high exposure face crystal phase and its unique hollow bowl-shaped tungsten oxide nano-spherical shell structure with rich porous structure. The technology has a far-reaching market application prospect in the fields of industrial production, environmental monitoring, indoor air quality monitoring, safety protection, and food quality testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is the XRD pattern of the sample; Figure 2 The SEM images of the samples are: (a) Comparative Example 1; (b) Example 1; (c) Example 2; (d) Example 3; (e) Example 4; (f) Comparative Example 2; (g) Comparative Example 3; (h) Comparative Example 4; (i) Comparative Example 5; Figure 3 TEM image of Example 1; Figure 4 The sensitivity of the sensor to 50 ppm dimethylamine at different temperatures; Figure 5 Sensitivity graph of the sensor to 50 ppm of different gases at 220°C; Figure 6 Sensitivity diagram of the sensor to different concentrations of dimethylamine at 220°C; Figure 7 Response-recovery curve of the sensor of Example 1 to 10 ppm dimethylamine at 220°C. DETAILED DESCRIPTION
[0014] The following is a further description of the implementation scheme of the present invention in conjunction with the accompanying drawings: The following examples provide detailed implementation methods and specific operating processes based on the technical solution of the present invention, but the protection scope of the present invention is not limited to the following examples. Example
[0015] A bowl-shaped WO3 sensor material assembled by particles and a preparation method thereof are as follows: ① Add PVA to deionized water, heat and stir for 4 h; ② Add ammonium paratungstate to the PVA solution and stir for 2 h; ③ Spray dry the mixed solution; ④ Heat the powder to dry and calcine to obtain the WO3 gas-sensitive material. The amount of PVA added in step 1 is 0.1 g; the amount of ammonium paratungstate added in step 2 is 0.8 g; the spray drying inlet temperature in step 3 is 160 ° C, the outlet temperature is 85 ° C, and the flow rate is 200 mL / h; the calcination temperature in step 4 is 450 ° C, and the calcination time is 2 h.
[0016] Finally, the diameter of the hollow bowl-shaped WO3 assembled by the prepared particles ranges from 3 to 5 μm; the specific surface area is 21 m 2 / g, and the surface particle diameter is about 50 nm.
[0017] The prepared material is made into a gas sensor with a indirectly heated structure according to the method in the claim, and the specific steps are as follows: Take 0.1 g of the annealed sample and pour it into an agate mortar. Use a dropper to draw pine oil into the mortar containing the sample and grind it into a thick paste. Use a toothpick to take a ceramic tube. Use tweezers to straighten the four platinum wires on the ceramic tube. Use a pre-cut bamboo stick to evenly apply the ground slurry on the ceramic outer wall, so that the gas sensor material forms a 0.2-0.4 mm dense oxide film on the outer wall surface. Then place it in a clean porcelain boat. After natural drying, put it in a muffle furnace together with the porcelain boat and calcine it at 350℃ for 2 hours. h, wait for it to cool naturally, take out the porcelain boat, take out the ceramic tube in the porcelain boat for later use; fix the base of the indirectly heated sensor element, and drop a drop of welding agent on the 6 electrode rods of the base in turn, use an electric welding pen to weld the two pairs of platinum wires of the ceramic tube to the tube seat, pass the heating resistor wire through the ceramic tube and weld the two ends to the other two poles of the tube seat; make a gas sensor with indirectly heated structure, finally mark it, insert the prepared gas sensitive element into the aging table in the aging machine, and start the gas sensitive test after aging for 14 days. Example
[0018] A bowl-shaped WO3 sensor material assembled by particles and a preparation method thereof are as follows: ① Add PVA to deionized water, heat and stir for 4 h; ② Add ammonium paratungstate to the PVA solution and stir for 2 h; ③ Spray dry the mixed solution; ④ Heat the powder to dry and calcine to obtain the WO3 gas sensitive sensor material. The amount of PVA added in step 1 is 0.2 g; the amount of ammonium paratungstate added in step 2 is 0.8 g; the spray drying inlet temperature in step 3 is 160 ° C, the outlet temperature is 85 ° C, and the flow rate is 200 mL / h; the calcination temperature in step 4 is 450 ° C, and the calcination time is 2 h.
[0019] The preparation was carried out by referring to the preparation method of the gas sensor with a indirectly heated structure in Example 1, and then a gas-sensing test was carried out. Example
[0020] The amount of PVA added was 0.3 g, and the other conditions were the same as in Example 1 to prepare a tungsten oxide gas-sensitive material. Example
[0021] The amount of PVA added was 0.4 g, and the other conditions were the same as in Example 1 to prepare a tungsten oxide gas-sensitive material.
[0022] Without adding PVA, other conditions were the same as in Example 1 to prepare tungsten oxide gas-sensitive material.
[0023] ① Add ammonium paratungstate to deionized water and stir for 2 h until dissolved; ② Add PVA to the ammonium paratungstate solution and heat and stir for 4 h; ③ Spray dry the mixed solution; ④ Heat the powder to dry and calcine to obtain WO3 gas sensitive sensing material. The amount of ammonium paratungstate added in step 1 is 0.8 g; the amount of PVA added in step 2 is 0.1 g; the spray drying inlet temperature in step 3 is 160℃, the outlet temperature is 85℃, and the flow rate is 200 mL / h; the calcination temperature in step 4 is 450℃, and the calcination time is 2 h.
[0024] The preparation was carried out by referring to the preparation method of the gas sensor with a indirectly heated structure in Example 1, and then a gas-sensing test was carried out.
[0025] The amount of PVA added was 0.2 g, and the other conditions were the same as those in Comparative Example 2 to prepare a tungsten oxide gas-sensitive material.
[0026] The amount of PVA added was 0.3 g, and the other conditions were the same as those in Comparative Example 2 to prepare a tungsten oxide gas-sensitive material.
[0027] The amount of PVA added was 0.4 g, and the other conditions were the same as those in Comparative Example 2 to prepare a tungsten oxide gas-sensitive material.
[0028] The morphology and structure of the materials prepared in the examples of the present invention and the comparative examples are tested and characterized by physical phase testing.
[0029] 1. Structural analysis The crystal structure of the samples was analyzed by X-ray diffraction (XRD) technique. Figure 1The X-ray diffraction (XRD) patterns of the materials are shown, and the crystal structures of all WO3 materials are highly consistent with WO3 (JPCD 20-1324). The 2θ angles at 23.083°, 23.707°, 24.099°, 26.587°, 28.766°, 33.331°, 33.640°, 34.022°, 35.525° and 41.524° correspond to the (001), (020), (200), (120), (111), (021), (201), (220), (121), and (221) planes of WO3, respectively. This shows that the prepared WO3 material has a high degree of crystallinity and no other elements are introduced. Compared with Comparative Examples 1 and 2, Example 1 has a relatively high (020) exposed crystal plane.
[0030] 2. Morphology analysis The morphology of the samples was examined using scanning electron microscopy and transmission electron microscopy. Figure 2 The observations in Figure 2 show that pure WO3 nanomaterials present a spherical nanostructure. The morphology of the WO3 nanomaterials treated with PVA presents a bowl-shaped structure. The initial spherical morphology of pure WO3 can be attributed to the intrinsic growth kinetics of WO3 nanomaterials under standard synthesis conditions. The introduction of PVA changes the nucleation and growth process. PVA acts as a capping agent and template agent. PVA can be adsorbed on specific crystal planes of WO3, changing its growth rate, leading to anisotropic growth and forming a bowl-shaped morphology. However, different morphologies are presented due to the different addition amounts and addition orders. Small particles of 50-100 nm are formed on the surface of the WO3 material prepared by dissolving ammonium paratungstate first and then dissolving PVA, while the surface of the WO3 material prepared by pyrolyzing PVA first and then dissolving ammonium paratungstate is smooth and does not form any particles. As the amount of PVA increases, the bowl-shaped structure less than 1 μm is gradually destroyed, and what remains are 2-5 μm WO3 materials. The possible reason is that the pyrolysis of PVA before the addition of ammonium paratungstate may create a template or matrix, which affects the subsequent growth of WO3, resulting in a smooth surface and no particle formation. At lower concentrations of PVA, the template effect is more obvious, forming a clear bowl-shaped structure. As the concentration of PVA increases, its excessive presence may break the balance of the system, destroy the formation of smaller structures, and lead to the formation of larger particles. Figure 3 This is the TEM image of Example 1. As can be seen from the figure, the bowl-shaped structure is hollow inside, and the surface is composed of 50-100 nanometer fine particles. A large number of rich porous structures are formed between the particles, which are conducive to the improvement of gas sensing performance. At the same time, it can be observed that a large number of lattice fringes representing the (020) crystal plane appear in its crystal phase structure, which is consistent with the XRD analysis. These special crystal plane structures have an important influence on the selectivity of specific gases.
[0031] Gas Sensitive Performance Test Figure 4 is the optimal operating temperature of the sensor of Example 1. It can be clearly seen from the results that the sensor of Example 1 exhibits a volcano-like response-temperature curve, with the highest response observed at 220° C. This phenomenon is attributed to the balance between the activity of the adsorbed oxygen and the desorption of the reactants on the sensing layer. Figure 5 The property of selectivity is of great significance in the field of gas sensors when considering their practical applications. Figure 5 The responses of sensors prepared with different samples to various gases at 220°C are shown, where the concentration of dimethylamine gas is 50 ppm, and the selectivity of the sensors to different volatile gases, including ethanol, toluene, methylamine, benzene, ammonia, methanol, benzene, and cyclohexane at 50 ppm. The results show that all sensors react most significantly to dimethylamine, and when exposed to 50 ppm of dimethylamine, the sensitivity of the sensor prepared in Example 1 is the highest, at 74. This response is significantly greater than that of other gases, which can be attributed to the strong reducing ability of dimethylamine.
[0032] Figure 6 The sensitivity diagram of the sensor to different concentrations of dimethylamine (1-50 ppm) at 220°C. The experimental results show that with the gradual increase of dimethylamine concentration, the response of all sensors increases significantly. Figure 7 The response-recovery curve of the sensor of Example 1 at 10 ppm dimethylamine is shown in the figure. The sensor of Example 1 can respond and recover quickly in a short time. In summary, the preparation method and application of a dimethylamine gas sensor material of the present invention have the following advantages: the material of the present invention does not require precious metal doping, has low production cost and is environmentally friendly, has a simple synthesis route, and has high repeatability. The prepared sensor has a fast response, a low detection line (1 ppm), and a high sensitivity value (74) when exposed to 50 ppm dimethylamine. The sensor also exhibits excellent selectivity and repeatability.
[0033] Tungsten oxide with a (020) highly exposed surface crystal phase structure has high selectivity and sensitivity to dimethylamine gas, which can be scientifically explained and theoretically based on the following aspects: (020) crystal plane usually has more surface defects and active sites, which can effectively adsorb dimethylamine molecules and promote the reaction between gas and tungsten oxide surface, thereby enhancing the sensitivity of the sensor. This crystal plane may have a stronger selective adsorption ability for the molecular structure of dimethylamine, and its interaction energy is higher than that of other gas molecules, resulting in a more significant conductivity change. During the adsorption process of dimethylamine molecules, the electronic structure of tungsten oxide will change, which will increase the carrier concentration and thus increase the change amplitude of conductivity. This mechanism provides theoretical support for high sensitivity. The (020) crystal plane may have faster reaction kinetics, which makes the adsorption and desorption process of dimethylamine molecules on the surface faster, further improving the response speed and sensitivity of the sensor. This crystal plane remains stable over a wide temperature range and adapts to different environmental conditions, thereby improving the reliability in practical applications.
[0034] In summary, the hollow bowl-shaped structure composed of particles and the (020) highly exposed surface crystal phase structure of tungsten oxide exhibit excellent selectivity and sensitivity in gas sensing applications for dimethylamine gas due to its special surface properties and electronic characteristics.
Claims
1. A method for preparing a high-performance bowl-shaped tungsten oxide material. It is characterized in that It is prepared from ammonium paratungstate and PVA by spray drying and high temperature annealing.
2. A method for preparing a high-performance bowl-shaped tungsten oxide material according to claim 1, It is characterized in that The specific steps include: ① Add ammonium paratungstate to deionized water and stir for 2 hours; ② After adding PVA, heat and stir evenly, and stir magnetically for 4 hours; ③ Spray dry the mixed solution; ④ Heat and dry the powder and calcine it to obtain tungsten oxide gas-sensitive material. Specifically, it is characterized in that in step 2.
3. A method for preparing a high-performance bowl-shaped tungsten oxide material according to claim 1 or 2, Features The amount of PVA added is 0-0.4 g; in step 3, the spray drying inlet temperature is 80-95°C, the outlet temperature is 140-160°C, and the flow rate is 100-200 mL / h; in step 4, the calcination temperature is 350-450°C, and the calcination time is 1-5 h.
4. The method for preparing a high-performance bowl-shaped tungsten oxide material according to claim 1 or 2, wherein the 3-5 μm bowl-shaped tungsten oxide composed of 50-100 nm particles has a specific surface area of 10-50 m 2 / g.
5. Tungsten oxide having a (020) high exposed surface crystal phase prepared by the preparation method according to claim 1 or 2.
6. Application of the method for preparing the bowl-shaped tungsten oxide material according to claim 5 in preparing a gas sensor.
7. The gas sensor made of the material described in claims 1-6 has high selectivity and sensitivity to dimethylamine gas.
